The effect of housing problems on older people’s subjective well-being in 21 European countries (Los efectos de los problemas de vivienda sobre el bienestar subjetivo de las personas mayores en 21 países europeos) - BAHNINI, Sara (2022)
Housing has been acknowledged as a basic human need with an impact on health and well-being. Since older people tend to be more exposed to features in their home environment, it is important to identify specific vulnerabilities. This study used cross- sectional data of 40,185 respondents from the 2014 European Social Survey Round 7 to explore the relationship between housing problems, age group (≤ 70 years and > 70 years) and evaluative (life satisfaction) and hedonic (happiness) dimensions of subjective well-being (SWB) of 21 European countries. Housing problems were significantly associated with lower levels of happiness and life satisfaction (LS) in a multilevel model. The age group was found to be a moderator of that association. When exposed to housing problems, older people (> 70 years) presented lower levels of happiness than younger adults (≤ 70 years). These findings shed light on the differentiation of age groups and call for maintenance and improvement of housing conditions in later life, aiming to promote well-being.